Crashworthiness analysis of two-layered corrugated sandwich panels under crushing loading. (December 2018) - Shu, Chengfu; Zhao, Shuyun; Hou, Shujuan
Abstract: In this study, the energy absorption characteristic of two-layered corrugated core sandwich panels with different arrangements under quasi-static compression loading were firstly investigated experimentally. Then compared the experimental results of these two different arrangements two-layered sandwich panels, it was found that the symmetric-arranged corrugated sandwich panel has better energy absorption characteristic, which is more than 17.17% at 6 mm displacement before densification stage compare to regularly-arranged. Numerical calculations were carried out and good agreement is achieved between the experimentally results and numerical results. Finally, parameter analysis and optimization study of the symmetric-arranged two-layered corrugated sandwich panel under planar impact was carried out with crashworthiness criteria by using finite element model and response surface method. The selection of parameters in optimization study were determined by parameter analysis. The size of sandwich panel was firstly optimized for maximizing specific energy absorption (SEA). Then the multi-objective optimization of core cell shape with optimal sandwich panel size was optimized by maximizing SEA and minimizing the peak force, a Non-dominated Sorting Genetic Algorithms (NSGA-II) code was used to perform the optimization process in a gradual evolution trend, which led to obtain the Pareto front that consisted of a set of optimal objective function vectors. Highlights: The energy absorption characteristic of different arrangement panels are investigated experimentally and numerically. The structural parameters that have effect on crashworthiness are determined by parameter analysis. Optimization design of symmetric-arranged panels under planar impact are carried out by using FE technique, DoE and RSM.